LABOR LAW, CLT AND THE 2017 BRAZILIAN LABOR REFORM - Fernandes João Renda Leal (PANORAMA OF BRAZILIAN LAW, 2018)
This study seeks to present to a foreign audience a brief description of the development of the Brazilian Labor Law, up to the Labor Reform approved by Law No. 13,467/2017, which significantly altered the nature of labor relations through amendments made to the texts of the “Consolidação das Leis do Trabalho - CLT” (Consolidation of Labor Laws - CLT), of Law No. 6,019/1974 and of other labor laws. The aim of this study is to analyze the Labor Reform within the historical context, with emphasis on its material aspects especially regarding the Collective Labor Law and Labor Union Law.